2015
DOI: 10.1007/s11906-015-0581-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Kidney Disease on Cardiac Structure and Function

Abstract: Chronic kidney disease (CKD), the presence of kidney dysfunction and/or damage, is a worldwide public health issue. Although CKD is independently associated with various subtypes of cardiovascular diseases, a recent international collaborative meta-analysis demonstrates that CKD is particularly strongly associated with heart failure, suggesting its critical impact on cardiac structure and function. Although numerous studies have investigated the association of CKD and cardiac structure and function, these stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 81 publications
4
19
0
Order By: Relevance
“…The negative correlation of serum creatinine and apoAI level confirms the above suggestions and also indicates that the reduced function of HDL particles may cause worsening kidney function [10][11][12][13]. The present study, hence, clearly demonstrates the important role of oxidative stress in the pathogenesis of chronic heart failure and progressive renal failure [21][22][23]. Beyond the aforementioned, we observed the highest serum creatinine, hsCRP, NTproBNP and LPO levels and the lowest serum apoAI and HDL-C concentrations in the NYHA 3 patients.…”
Section: Discussionsupporting
confidence: 88%
“…The negative correlation of serum creatinine and apoAI level confirms the above suggestions and also indicates that the reduced function of HDL particles may cause worsening kidney function [10][11][12][13]. The present study, hence, clearly demonstrates the important role of oxidative stress in the pathogenesis of chronic heart failure and progressive renal failure [21][22][23]. Beyond the aforementioned, we observed the highest serum creatinine, hsCRP, NTproBNP and LPO levels and the lowest serum apoAI and HDL-C concentrations in the NYHA 3 patients.…”
Section: Discussionsupporting
confidence: 88%
“…There are conflicting findings in the literature with respect to the association between UACR and LV systolic function, 8 likely in part due to the lack of sensitivity of LVEF for mild systolic dysfunction. Our inclusion of strain allowed us to better characterize systolic dysfunction as compared with most existing studies, and we found that microalbuminuria was significantly associated with impaired strain.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In non-Hispanic populations, the urine albumin-to-creatinine ratio (UACR), a measure of proteinuria and marker of kidney damage, has been associated with cardiovascular disease (CVD) mortality and heart failure, 6,7 as well as subclinical measures of cardiac structure and function. 8 To our knowledge, no studies have examined the association between albuminuria and cardiac dysfunction in U.S. Hispanics/Latinos, despite a disproportionate burden of risk factors leading to chronic kidney disease in some Hispanic groups. 9,10 Using data from the Echocardiographic Study of Latinos (Echo-SOL), we examined the association between UACR and measures of cardiac structure and function among 1,815 Hispanic/Latino individuals who underwent a standardized 2-D echocardiography protocol, including speckle-tracking analysis for measurement of longitudinal strain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CKD patients frequently develop left ventricular hypertrophy, hypertension, valvular heart disease, left ventricular systolic failure, diastolic failure, arrhythmias, accelerated atherosclerosis progression, ischemic artery disease, and sudden cardiac death. [9][10][11][12][13] Some therapeutic strategies, such as the blockage of reninangiotensin-aldosterone system, allow to slow down but not to fully halt CKD progression. For this reason, other potential treatments are currently under investigation but conclusive results are still lacking.…”
Section: Introduction To the Epidemiology And Management Issues In Ckdmentioning
confidence: 99%